Penurunan Kromium (Cr) dalam Limbah Cair Proses Penyamakan Kulit Menggunakan Senyawa Alkali Ca(OH)2, NaOH, dan NaHCO3 (Studi Kasus di Pt Trimulyo Kencana Mas Semarang) - Joko, Tri (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2003)
ABTRACT Background : One of the industrial type which use hazardous materials in its production process is leather tanning industry, by using chromium compound (Cr). Chromium is a heavy metal compound which recognized has a high poison energy. Result of analysis of sampel industrial liquid waste of leather tanning of PT Trimulyo Kencana Mas (TKM) Semarang showed that total chromium concervation was 49,575 m/l. This total Chromium rate was still above the standard quality of which enabled maximal 2,0 mg/l, according to Kep51/MENLH/110/1995. Alkali compound of Ca(OH)2, NaOH and NaHC03 is chemicals able to be used for the processing of industrial liquid waste of pregnant leather tanning of chromium, functioning to boost up condensation pH andprecipitated chromium so that obtained chrome in theform of hydroxide chromium (Cr(OH)3). Methods : which used in this research is (quasi experimental), with experiment variable repeated or referred as one group pretest ‑ posttest design. Results : of this research showed that optimum pH for the compound of each alkali at condition of pH 8, with the efficiency dissociation of chromium was equal to 99,28 % by using alkali compound of Ca(OH)2 and of NaOH, while usage of NaHC03 equal to 98,50 %. Conclusions: Alkali compound of Ca(OH)2, NaOH and NaHCO3 can degrade chromium concentration (Cr) in liquid waste with high efficiency, that is reaching under standard quality. The most effective Compound of Alkali, evaluated from the technical aspect for the degradation of chromium concentration in liquid waste is NaOH, because with only small dose can dissociate chromium in liquid waste with high efficiency (99,28 %), For economic reason and recommendation for application in the field is Ca(OH)2. Keyword : Efficiency Ca(OH)2,, hydroxide chromium, NaHCO3, NaOH, pH, Chromium Compound